Will the Growth of the BRICs Cause a Shift in the Global Balance of Economic Power in the 21st Century?. Issue 4 (1st October 2016) - Siddiqui, Kalim
Abstract: Some 42% of the world's population (i.e., 3 billion people) live in Brazil, Russia, India, and China, collectively known as BRICs. Of these four, India and Brazil also have a higher than average birth rate. The combined economy of the BRICs made up 25.6% of the global GDP in 2015 and has been projected to increase to 33% by 2020. Studying the BRICs economies is important for a number of reasons, including their rapid economic growth rates, large populations, and fast-growing markets for goods and capital. Their average per capita annual income ranges from about US3, 000 to nearly US15, 000 in PPP terms. However, in 2015 their average annual GDP growth exceeded 6%, which is much higher than the 1.9% of the OECD countries. It is estimated that their share in the world economy could double over the next two decades, from 25.6% to 40%.